Políticas públicas de acesso à informação na educação superior: proposta de diretrizes para criação do Arquivo Central da Universidade Federal do Amapá - Pacote, Kawan de Souza (2023)
This research takes a look at Archives within a university environment. In this work we analyze how the absence of a Central Archive impacts access to information at the Federal University of Amapá Foundation (UNIFAP). To this end, we use the inductive method as a general methodology, as a method of procedures. The research is configured as a case study, in terms of the type of research it is of an applied nature and a qualitative approach, in terms of objectives it is exploratory and in terms of technical procedures we use the bibliographic, documentary and case study method. The general objective of the research is to analyze how access to information is given at UNIFAP in the absence of a Central Archive. The research has specific objectives to investigate the flow of information within the scope of UNIFAP, point out the barriers that prevent access to information through the absence of a Central Archive, characterize the use of legislation in UNIFAP through the application of a questionnaire, understand the Archive Central and its importance in access to information within the scope of UNIFAP and, finally, propose guidelines for the creation of the Central Archive that will be the product of this research.